Estudio de procesos de fitorremediación aplicados en suelos contaminados con hidrocarburos por el desarrollo de actividades de las EDS (2021)
In this monograph we sought to carry out a bibliographic study of the most outstanding methods in phytoremediation processes that contribute to the decontamination of affected soils, basically due to the development of industrial activities that generate direct alterations in the soil layers.